Organization of Healthy Catering in Russian Universities Using Vending Technologies - BELYAEVA, M. A.; BURLANKOV, S. P.; GAJOUR, A. A.; PEROV, V. I.; SOKOLOV, A. Yu. (Journal of Environmental Management and Tourism; Vol 9 No 1 (2018): JEMT Volume IX Issue 1(25) Spring 2018DO - 10.14505//jemt.v9.1(25).14, 2018)
Relevance of the research: at present moment, healthy catering is a relevant issue for higher education institutions; this includes ensuring the quality of food and automating the sale of set lunches through vending machines, thereby providing students with a better access to healthy food and taking into account consumer preferences. The article presents a comparative analysis of the organization of healthy catering by using vending technologies not only in leading Russian universities, but also at the international level. Goal of the research: to develop diets for male and female students, as well as the mechanisms for their implementation, mainly using vending machines for selling set breakfasts and lunches that meet the regulatory requirements for developed diets. Research methods: the study involved using a range of questionnaires and analyzing preferences of students and university staff. Conducting marketing research, the authors applied methods of market analysis, as well as on-line questionnaires. The research sample included 230 students. Results of the study: the article considers in detail catering at the Plekhanov Russian University of Economics. To compare the results, the authors also studied other six leading universities of Moscow and the data from a number of large international universities. It was determined that most universities require the development of healthy catering, as well as improving the service. These problems are especially acute in the sphere of social catering, and namely in the university catering. Therefore, the authors explored the following aspects: the market situation with the demand for catering services in universities (Russian and international); conducting polls, interviewing the youth to assess the quality of food, service, range of meals, ways of selling dishes and others. The best way to improve catering at universities seems to be through using vending machines, pizza mats and other innovations. However, there are some problems associated with the maintenance of vending machines, which implies their rational location. In addition, it is necessary to develop the required product range, and solve the related tasks of batching, packaging, and logistics.